Karakteristik Sensori dan Hedonik pada Pacid Kule Ikan Mas (Cyprinus Carpio) Fermentasi - Pramesti, Yuli; Anjani, Gemala; Hunaefi, Dase (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the best and most preferred sensory and hedonic characteristics of fermented Pacik kule goldfish (cyprinus carpio) typical of the Alas tribe, Southeast Aceh district. The research method was an experiment using a completely randomized design (CRD) with 3 treatments for the storage time of Pacik kule fish typical of Aceh. With 2 repetitions. Statistical tests for sensory use the Kruskal Wallis test and for hedonic tests use the Fiedman test to see test ranking. The results showed that the sensory characteristics for aroma attributes were different for each sample (p = 0.03 < 0.05). For sensory taste, there are differences in each attribute (p = 0.01 < 0.05). The hedonic test of color, aroma, taste and texture that was most liked by the panelists was found in the F2 fermentation time (12 hour fermentation), with a very like classification and the lowest classification, namely F3 (36 hour fermentation) with a dislike classification. The research conclusion is that the aroma sensory characteristic with the highest intensity is the very aromatic attribute of Pacik kule spices typical of Southeast Aceh, for the taste sensory characteristic with the highest intensity is the characteristic fish taste attribute. The best hedonic test was found in the F2 treatment or fermentation for 12 hours. Keywords: Hedonic, Pacik kule, Sensory